Correction: Individual single-crystal nanowires as electrodes for organic single-crystal nanodevices. Issue 37 (7th October 2015) - Wang, Guorui; Tang, Qingxin; Tong, Yanhong; Hu, Wenping; Liu, Yichun
<x xml:space="preserve">Abstract</x> Correction for 'Individual single-crystal nanowires as electrodes for organic single-crystal nanodevices' by Guorui Wang et al., J. Mater. Chem. C, 2015, DOI: ; Web: 10.1039/c5tc01920f.